OPTIMIZATION OF AGRICULTURAL LAND USE THROUGH WATER SAVING AND ENVIRONMENTALLY FRIENDLY AGRICULTURE - Namah, Chris N.; Abineno, Jemseng C.; Siviardus Marjaya; Haryati M. Sengadji; Melgiana S. Medah; Dina V. Sinlae (Asosiasi Dosen Muda Indonesia, 2024)
Integrated agriculture is a combination of two activities, namely the agricultural Integrated agriculture is a combination of two activities, namely the agricultural sector and the livestock sector and is sometimes also known as the Livestock and Crop Integration System. By mastering technology, farmers can manage their resources more effectively, reduce dependence on outside parties, and create added value from their agricultural products. agriculture, but also as a driving force for a sustainable local economy. The aim of the research is to describe the use of agricultural technology through the application of water-saving and environmentally friendly agricultural technology and to realize community economic independence and preserve natural resources (soil nutrients). The research was carried out at the Tnao Mat Farmers Group Garden, III Bieto Hamlet, Niuk Baun Village, West Amaraasi District, Kupang Regency. The data collection methods used were observation, interviews and documentation. Next, experiments were carried out to produce Organic Fertilizer (Bokashi, POC and Drip Irrigation). The results obtained are that the environmentally friendly agricultural model has strengths greater than its weaknesses, as well as its opportunities greater than its threats. So farmers can be directed to dare to try environmentally friendly agricultural models to reduce production costs and increase quality agricultural products. Keywords: Production, Cucumis sativus L, SP-36, Cow manure